Benefits of green building from client's perspective / Norazlin Mat Salleh ... [et al.] - Norazlin, Mat Salleh; Nik Noor Hazleeda, Baharuddin; Shahela, Mamter; Mohd Esham, Mamat (2015)
Sustainable development has been highlighted in the 11th Malaysia Plan, 2016-2020 to make sure all development meets the needs of the present without compromising the ability of future generations to meet their own needs. An example is the development of green building refers to both a structure and the use of processes that are environmentally responsible and resource-efficient throughout a building's life-cycle: from siting to design, construction, operation, maintenance, renovation, and demolition. Therefore, this paper presents the benefits of green building from the client’s perspective. All variables have been identified from available literature and from that a set of questionnaire was built and sent to 32 clients around Selangor. The data was analyzed using the Statistical Package for Social Sciences (SPSS) and Mean. The research shows that limiting the building impact on the environment during the building’s lifecycle and protecting occupants’ health are the first and second ranking. This paper will be useful and inspirational to other clients to develop more green buildings due to their many benefits.